An alternative approach to the replacement of missing teeth with adhesive bridges and unilateral RPD metal frames: a case report - Dammar, Irfan; Ajmal, Andi (Hasanuddin University, 2020)
Objects : The purpose of this case report is to restore healthy tooth function with compromised tooth replacement so that patients are more confident and chew food well, a good choice of denture selection methods are good for patients with loss of one anterior maxillary tooth with adhesive bridge denture treatment and choice of removable partial denture metal frames as an alternative solution to the replacement of mandibular posterior teeth.Methods : A 65 years old female patient came to Dental Hospital Hasanuddin University with complaints of a loose maxillary partial denture complaining and difficulty chewing food because her posterior teeth had been removed +/- 7 years ago and her anterior teeth were removed about +/- 5 years ago. Want to replace the old removable partial denture with fixed denture for maxillary anterior teeth and also want to make a partial denture metal frames for mandibular teeth.Results : The case of loss of one maxillary anterior tooth was successful with the treatment of adhesive bridge dentures and the use of a removable partial denture metal frames a more stable and retentive mandibular posterior tooth loss that showed a better prognosis.Conclusion : Use of adhesive bridge dentures for maxillary anterior teeth and partial dentures metal frames for posterior mandibular teeth provides satisfaction for patients because it can overcome aesthetic problems and improve good phonetic and masticatory functions.